Pathogenicity of IgG in patients with IgG4-related disease. Issue 8 (10th March 2016) - Shiokawa, Masahiro; Kodama, Yuzo; Kuriyama, Katsutoshi; Yoshimura, Kenichi; Tomono, Teruko; Morita, Toshihiro; Kakiuchi, Nobuyuki; Matsumori, Tomoaki; Mima, Atsushi; Nishikawa, Yoshihiro; Ueda, Tatsuki; Tsuda, Motoyuki; et al.
Abstract : Objective: IgG4-related disease (IgG4-RD) is a systemic disease characterised by elevated serum IgG4 and IgG4-positive lymphoplasmacytic infiltration in the affected tissues. The pathogenic role of IgGs, including IgG4, in patients with IgG4-RD, however, is unknown. Design: We examined the pathogenic activity of circulating IgGs in patients with IgG4-RD by injecting their IgGs into neonatal male Balb/c mice. Binding of patient IgGs to pancreatic tissue was also analysed in an ex vivo mouse organ culture model and in tissue samples from patients with autoimmune pancreatitis (AIP). Results: Subcutaneous injection of patient IgG, but not control IgG, resulted in pancreatic and salivary gland injuries. Pancreatic injury was also induced by injecting patient IgG1 or IgG4, with more destructive changes induced by IgG1 than by IgG4. The potent pathogenic activity of patient IgG1 was significantly inhibited by simultaneous injection of patient IgG4. Binding of patient IgG, especially IgG1 and IgG4, to pancreatic tissue was confirmed in both the mouse model and AIP tissue samples. Conclusions: IgG1 and IgG4 from patients with IgG4-RD have pathogenic activities through binding affected tissues in neonatal mice.